Harnessing the expert knowledge within PABRA: tracking diffusion of improved varieties - Muthoni Andriatsitohaina, Rachel; Ongom, Bonny; Muwanika, Roland; Farrow, Andrew; Andrade, Robert Santiago (Pan-Africa Bean Research Alliance, 2017)
The Diffusion of Improved Varieties in Africa (DIIVA) is a cross-center CGIAR project that has been developed to attain a wider understanding of the impact of food-crop genetic research in priority country-by-commodity combinations in Sub-Saharan Africa. One of its objectives is to develop a comprehensive evidence-based collection on the performance of bean genetic improvement in 10 countries for the period 1999 to 2009. The project recognizes that a comprehensive analytical basis for perceptions of crop improvement research and its diffusion in sub Saharan Africa is incomplete. Through this effort CIAT seeks to provide an up to date status for the bean crop.